Change Detection by Using Multitemporal Satellite Image for Region of Samara City (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Detecting changes is an immportant part in processing satellite images in remote sensing . The change detection method was applied to an area of the city of samaraa. These changes that occur during acertain peroid of time .Through this paper the changes in the study area were revealed using the subtraction method for two colored merged images for three band of 3,5,7 . The changes were observed by calculating the standard devition ,which increased in the second time compared to the first time ,as well as distinguishing the colors of the image that were colored in distinct colors such as blue which indicate low areas and pink indicates agricultural and wet areas